PHARMACEUTICAL EVALUATION AND TOXICOLOGICAL QUANTIFICATION OF HEAVY METALS AND ADULTERATED ALLOPATHIC CONTENTS IN RAWAND FINISHED DOSAGE FORM OF ANTIHYPERTENSIVE HERBAL PRODUCTS - Khan, Muhammad Asif; Badshah, Amir; Shahid, Muhammad (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Herbal products of questionable quality create major concern for human population since their production is often not controlled and regulated. Material and Methods: Antihypertensive herbal products were subjected to pharmaceutical quality control parameters specified in Pharmacopoeias, toxic quantification of heavy metals by flame atomic absorption spectrophotometer and adulterated allopathic contents were quantified using advanced HPLC techniques. Results: A lot of variations in pharmaceutical parameters like moisture contents and LOD% values were observed. Also deviations to a greater extent in weight variation, (P1, P2, P6, P12, P16, P17, P19, and P20), and hardness of the tablets of products (P1, P3, P8 and P11) were found. Friability of tablets of the Products (P3, P9 and P11) was found failed. Heavy metals i-e Fe (1597.20ppm, 1648ppm) in P5, P9, Pb (61.32ppm, 16.59 ppm) in P5, Cr (96.91ppm ,108.48 ppm) in P4, P14, Cd (39.53ppm, 32.31 ppm) in P11, P12, Cu (28.22ppm, 21.04 ppm) in P15, P17, Zn (80.31ppm,76.27 ppm) in P15, P16, Ni (45.46ppm,22.18ppm) in P9, P13 in toxic concentrations were detected. Adulterated allopathic contents of Amlpdopine in higher quantities, administered according to manufacturer dose were found in P12 (20.30 mg/day), Verapamil in P2 (93.50 mg/day), Nifedipine (38.65 mg/day) in P6. Products P4, P5 and P7 were found to have a combination of Amlodipine and Hydrochlorothiazide and higher concentrations were found in P5 (10.72 mg/day, 24.75 mg/day). Conclusion:. The antihypertensive herbal products contained different kind of adulterants. Our findings suggest that effective regulatory measures should be put in place to address this problem. This will help to decrease the toxic effects of these remedies and increase the commercialization, internationalization and harmonization of antihypertensive herbal products.